The The determinants of accounting student perceptions of earnings management in Indonesia - Suwadji, Sukma Annisa; Lestari, Rahayu; Muthmainnah, Dewi Refianingrum; Na'im, Ainun (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study aims to investigate the influence of religiosity, gender, ethical orientation (idealism and relativism), and professional commitment on accounting students’ perceptions of earnings management.Design/Methodology/Approach: A quantitative approach was employed through the distribution of structured questionnaires to accounting students from several universities in Indonesia. The collected data were analyzed using multiple linear regression analysis to determine the relationship between the independent variables and perceptions of earnings management.Research findings: The findings show that religiosity has a influence on perceptions of earnings management, meaning students with higher religious values tend to view earnings management as unethical. Gender differences also play a significant role, where female students demonstrate stricter ethical views compared to male students. Idealistic ethical orientation is positively associated with ethical perceptions, whereas relativistic orientation does not have a significant effect. Moreover, professional commitment negatively affects the acceptance of earnings management practices.Theoretical contribution/ Originality: This study contributes to the literature on accounting ethics by providing empirical evidence of how individual characteristics and ethical values influence the ethical judgment of future accounting professionals regarding earnings management.Practitioner/Policy implication: The findings suggest that ethical training in accounting education should consider personal values and ethical orientations. Gender-responsive and value-based ethics education may enhance ethical standards in the profession.Research Limitations/Implications: The study is limited to accounting students and may not fully reflect the perceptions of practitioners in the field. Future research could expand the sample to include professionals for broader generalizability.